The efficacy and safety of external cephalic version after a previous caesarean delivery. (14th September 2016) - Weill, Yishay; Pollack, Raphael N.
Abstract : Background: External cephalic version (ECV) in the presence of a uterine scar is still considered a relative contraindication despite encouraging studies of the efficacy and safety of this procedure. We present our experience with this patient population, which is the largest cohort published to date. Aims: To evaluate the efficacy and safety of ECV in the setting of a prior caesarean delivery. Materials and methods: A total of 158 patients with a fetus presenting as breech, who had an unscarred uterus, had an ECV performed. Similarly, 158 patients with a fetus presenting as breech, and who had undergone a prior caesarean delivery also underwent an ECV. Outcomes were compared. Results: ECV was successfully performed in 136/158 (86.1%) patients in the control group. Of these patients, 6/136 (4.4%) delivered by caesarean delivery. In the study group, 117/158 (74.1%) patients had a successful ECV performed. Of these patients, 12/117 (10.3%) delivered by caesarean delivery. There were no significant complications in either of the groups. Conclusions: ECV may be successfully performed in patients with a previous caesarean delivery. It is associated with a high success rate, and is not associated with an increase in complications.